من فلسفة الإبداع إلى إبداع الفلسفة: قراءة في الإنجاز الفكري لطه عبد الرحمن - عبد الملك بومنجل (International Institute of Islamic Thought, 2012)
قصدُنا بهذا البحث الوقوف عند حقيقة جوهرية في فكر طه عبد الرحمن، وهي أنّه مسكون بهمٍّ فكري حضاري مُلِحّ، هو همّ الإبداع الفلسفي الأصيل، الذي يُقدِّم الجواب العربي الإسلامي عن أسئلة العصر؛ لذلك تراه مُتحِّركاً بين رسالتين: الأولى النظر الفلسفي في حقيقة الإبداع: ما هي؟ وكيف تتجسد؟ وهل الفكر العربي المعاصر مُبِدع أم مُقلِّد؟ والثانية هي إبداع فلسفة حقيقةٍ بمعناها؛ فهي اجتهاد فكري أصيل، وبناء فلسفي متماسك. ومتأصّلة في تربتها؛ فهي عربية اللغة والبيان والمصطلح، إسلامية المنطق والرؤية والروح. ومتصلة بحاضرها؛ فهي تخاطب العصر بالمنهج الفكري الذي يناسبه، وتعالج مشكلاته بالمنطق الفلسفي الذي يفهمه. The aim of this article is to understand the essence of Taha Abdurrahman's thought. This philosopher is haunted by an urgent intellectual and civilizational concern; it is the original philosophical creativity which provides Arabic Islamic response to contemporary questions. He has been moving between two messages: The first one is the philosophical perspective of creativity; what is it? How does it materialize? Is contemporary Arabic though creative or imitative? The second message is the creative production of a real philosophy; an original intellectual ijtihad, and coherent philosophical structure; a philosophy that is rooted deeply in its natural soil; Arabic in language and terminology, Islamic in its vision and spirit; addresses contemporary time with proper intellectual method, and solves its problems using the appropriate logic.